Assessing the size of shadow economic activity in Malaysia based on the modified money demand model approach with structural break - Gamal, Awadh Ahmed Mohammed; Salem, Sultan Ali Mohammed; Tha, Gan Pei; Jalil, Norasibah Abdul; Umar, Mohammed (Asian Journal of Economic Modelling, 2024)
This paper aims to address those methodological issues by exclusively applying the newest modification to the Money Demand Model (MDM) in the form of the autoregressive distributed lag (ARDL) approach to estimate the Malaysian shadow economy (SE) from 1985 to 2020. Methodological errors and spurious regression issues hindered earlier studies on the Malaysian SE. Some studies included Malaysia in their analyses alongside other Asian countries with similar levels of development, without accounting for the distinct economic environments of these countries. This study accounts for the influence of economic uncertainty (EU) and structural breaks. The study finds that Malaysia's SE averaged 40.8% of its official gross domestic product (GDP), peaking in 1995–1996, after which it gradually declined and stabilized around 39.4% of GDP. This substantial size highlights the critical need for tailored economic policies to manage SE growth effectively. The findings not only provide a clearer understanding of the SE’s trajectory but also emphasize the importance of addressing illicit activities, particularly in connection to public spending and corruption. Future research should prioritize examining these hidden activities to uncover how the shadow economy impedes Malaysia’s progression toward becoming a developed nation and how informality affects broader economic progress.